Effects of Curcumin Supplementation on Exercise-Induced Oxidative Stress in Humans - Takahashi, M.; Suzuki, K.; Kim, H. K.; Otsuka, Y.; Imaizumi, A.; Miyashita, M.; Sakamoto, S. (International Journal of Sports Medicine, 2014)
The purpose of this study was to investigate the effects of curcumin supplementation on exercise-induced oxidative stress in humans. 10 male participants, ages 26.8±2.0 years (mean±SE), completed 3 trials in a random order: (1) placebo (control), (2) single (only before exercise) and (3) double (before and immediately after exercise) curcumin supplementation trials. Each participant received oral administration of 90 mg of curcumin or the placebo 2h before exercise and immediately after exercise. Each participant walked or ran at 65% of V˙2max on a treadmill for 60min. Blood samples were collected pre-exercise, immediately after exercise and 2h after exercise. The concentrations of serum derivatives of reactive oxygen metabolites measured immediately after exercise were significantly higher than pre-exercise values in the placebo trial (308.8±12.9 U. CARR, P<0.05), but not in the single (259.9±17.1 U. CARR) or double (273.6±19.7 U. CARR) curcumin supplementation trials. Serum biological antioxidant potential concentrations measured immediately after exercise were significantly elevated in the single and double curcumin supplementation trials compared with pre-exercise values (P<0.05). These findings indicate that curcumin supplementation can attenuate exercise-induced oxidative stress by increasing blood antioxidant capacity.
Keywords: curcumin; oxidative stress; antioxidant capacity; endurance exercise